Geochemical evaluation of the middle Magdalena basin, Colombia - Ramón, J. C.; Dzou, L.; Giraldo, B. (CT&F - Ciencia, Tecnología y Futuro, 1997)
The chemical composition of 25 crude oils from Tertiary reservoirs and 12 rock extracts from five organic-rich Cretaceous formations in the Middle Magdalena Basin, Colombia were studied in detail by geochemical methods in order to understand their genetic relationships. The oils have been geochemically classified into four main groups based on the sulfur content, pristane/phytane, dibenzothiophene/phenanthrene, concentrations of oleanane and terpane distributions. Each group occur in different geographic locations. Oils were mainly derived from calcareous, siliciclastic and mixture of these two fades of the Upper Cretaceous La Luna Formation. Source-oil correlation is supported bysterane and terpane distributions of and carbon isotope ratios. Some oils in the eastern margin contain relatively higher concentrations of higher plant indicators than the remaining oil samples. The molecular compositions of the oils observed in this study appear to be consistent with the inferred depositional sequence of anoxic marine/pelagic carbonate fades in the north/western sector of the Middle Magdalena, while the eastern sector received a higher proportion of clastic input. This documentation supports the interpretation that the Middle Magdalena oils have been generated "locally", as opposed to have migrated from the region of the Eastern Cordillera. Biomarker maturity parameters indicate that the majority of oils were generated in the early thermal maturity oil window except the Colorado-38 oil which was generated in the middle thermal maturity oil window. Oil maturity data also supports the short migration distances of oils from the early-mature source rocks to the reservoir rocks. The composition of some oils (e.g., La Cira, Infantas, Conde and Bonanza) is unusual in that gas chromatographic data contains an n-alkane and isoprenoid distribution normally associated with moderately degraded oils, but they also contain a relatively high abundance of gasoline hydrocarbons. This particular gas chromatographic pattern may be explained by the addition of migrant gas/ condensate to the "in situ" biodegraded oils. Secondary condensates may also have charged the less biodegraded oils (e.g., Cantagallo-23 and Casabe-471), which could explain the "V" pattern of the n-alkane distribution. This phenomena is observed in productive basins in other parts of the world. The range of oil gravities measured in the Middle Magdalena Basin is attributed to organic fades variations, different levels of biodegradation and late charge of condensate rather than to thermal maturity and migration-related effects.